2012
DOI: 10.1039/c2cc17859a
|View full text |Cite
|
Sign up to set email alerts
|

Pd-catalysed synthesis of isoquinolinones and analogues via C–H and N–H bonds double activation

Abstract: An atom economical synthesis of isoquinolinones and analogues via ligand-free Pd-catalysed C-H and N-H double activation has been developed. A series of isoquinolinones were obtained in good to excellent yields. Good regioselectivities were also observed during the activation reactions with unsymmetrical alkynes. A practical one-pot procedure for the preparation of N-H isoquinolinones is also described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
10

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(80 citation statements)
references
References 36 publications
3
67
0
10
Order By: Relevance
“…45 The procedure is performed using Pd(OAc) 2 as catalyst (10 mol%) in the presence of dihydrated sodium iodide as additive, in DMF at 120 ºC, as illustrated in Scheme 16…”
Section: Isoquinolinones Can Be Prepared From N-methoxy-or N-isopropomentioning
confidence: 99%
“…45 The procedure is performed using Pd(OAc) 2 as catalyst (10 mol%) in the presence of dihydrated sodium iodide as additive, in DMF at 120 ºC, as illustrated in Scheme 16…”
Section: Isoquinolinones Can Be Prepared From N-methoxy-or N-isopropomentioning
confidence: 99%
“…In this mild iodobenzene-catalyzed annulation process, a series of readily available symmetrical and non-symmetrical internal alkynes were coupled with N-alkoxybenzamide derivatives 109 in the presence of peracetic acid as an oxidant (Scheme 27). This result is indeed highly intriguing considering the fact that such annulation reactions have previously been achieved only through expensive transition metal (Pd, Rh, Ni, Ru) catalyzed processes requiring high temperatures, external oxidants, and longer reaction times [77][78][79][80][81][82]. The mechanistic cycle of this transformation presumably begins with the formation of a nitrenium ion 111, in a manner similar to that described in Sect.…”
Section: Intermolecular C-c/c-n Bond Annulationmentioning
confidence: 65%
“…Initially, the minor product was misassigned as a C–N cyclization product. This side product was later correctly identified by Huang [22] to arise from C–O cyclization with the retention of the N–OMe moiety (Table 1) which has significant mechanistic implication. Intriguingly, the O-cyclized product appears to be formed through a direct reductive elimination from a Rh(III) center forging the C–O bond, which is consistent with an alkali carboxylate-type coordination mode (Scheme 3).…”
Section: Rhodium Catalysismentioning
confidence: 86%
“…[22] Interestingly, the examination of additives showed that alkali metal salts were beneficial to this reaction. Among these salts, NaI·2H 2 O was the most effective additive.…”
Section: Palladium Catalysismentioning
confidence: 99%